ANALISIS PENGARUH STRATEGI PRODUK DIGITAL DAN STRATEGI PROMOSI BERBASIS DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK PENDIDIKAN PROVINSI BALI - Desak Putu Ramayanti; Ni Luh Indiani; I Nyoman Wahyu Widiana (Nusantara Hasana Journal, 2024)
This research aims to determine the influence of Digital Product Strategy and Digital Marketing-Based Promotion Strategy on Consumer Purchasing Decisions on Bali Province Educational Products. This research was structured descriptively using a quantitative approach method. In this research, the data collection instrument is a questionnaire to obtain information about a number of respondents representing a certain population and then statistical data analysis (SPSS) will be carried out to test the hypothesis that has been proposed. The results of this research found that Digital Product Strategy has a positive effect on Consumer Purchasing Decisions on Bali Province Education products. From the results, the t-count value for the Digital Product Strategy variable is 5.294, indicating that the t-count is greater than the t table (5.294 > 1.996), with a significant value of 0.000, smaller than 0.05 (0.000 < 0.05), and the regression coefficient has a positive value of 0.377. Digital Promotion Strategy has a negative effect on Consumer Purchasing Decisions on Bali Province Education products with a calculated t value of the work environment variable of 3.466, indicating that the calculated t is greater than the T table (3.466 > 1.996), with a sig value of 0.001 < 0.05, and The regression coefficient has a positive value of 0.209. And Digital Product Strategy, Digital Promotion Strategy have a joint (simultaneous) influence on Consumer Purchasing Decisions on Bali Province Education products seen from the output data showing an R-Square value of 0.554, this means that the Digital Product Strategy and Digital Promotion Strategy variables, influences Consumer Purchasing Decisions (Y) by 55.4%, the remainder influences other variables not examined in this thesis.